Application of nanotechnology in dairy industry-prospects and challenges-A Review - Radha et al., K (Indian Journal of Dairy Science, 2014)
Nanotechnology applications are expected to revolutionize the food and dairy sector in the near future. The potential applications include superior processing techniques, improved food contact materials, better quality, shelf-life and safety of dairy and food products and novel packaging materials with better mechanical, barrier and antimicrobial properties. Recently, there is considerable interest in exploring the potential of nanotechnology in encapsulation and delivery of biologically active substances, enhancing the flavour and other sensory characteristics of foods and introduce antibacterial nanostructures into packaging. By reducing particle size, nanotechnology can improve the properties of bioactive compounds like delivery properties, solubility and absorption through cells. However, consumer concerns about the potential negative effects of nanotechnology-based delivery systems on human health will need to be addressed before commercial exploitation. This article comprehensively reviews theapplication of nanotechnology in dairy and food-related systems, focusing specifically on applications which are most likely to be commercialized in the immediate future